Behavioral market intelligence and its implications for seed systems development - Trachtman, Carly; Kramer, Berber; Demont, Matty (CGIAR System Organization, 2022)
In many countries, varietal turnover rates are stubbornly low in seed systems that target smallholder farmers. While there are several factors that contribute to low turnover, two important behavioral factors that limit adoption of new varieties are the difficulties that farmers may face in learning about new varieties and their hesitancy to assume risks associated with investing in new varieties. In this brief, we review part of the literature on behavioral constraints that result in slow varietal turnover and discuss the interventions that the CGIAR Initiative on Market Intelligence and Product Profiling for Impactful Breeding will be testing to overcome these behavioral barriers. We highlight areas for innovation to facilitate farmers’ learning about new varieties, including leveraging social networks and information and communication technologies (ICT), and to strengthen farmers’ ability to manage risks associated with investing in new varieties, including facilitation of experimentation, insurance and consumer marketing.